2005
DOI: 10.1016/j.jcrs.2004.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bag-in-the-lens implantation on posterior capsule opacification in human donor eyes and rabbit eyes

Abstract: Bag-in-the-lens implantation was highly effective in preventing PCO in vitro and in vivo provided the anterior and posterior capsules were secured properly in the peripheral groove of the IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…14,19 -23 With respect to testing IOLs using such systems, the body of literature is limited. 14,19,22,24 Liu et al 14 initially demonstrated that an IOL could impede growth to some degree using the human capsular bag system developed in Norwich. In the present study, we made a modification in the protocol such that the capsular bag containing the IOL was inverted, resulting in the anterior capsule being closest to the plastic dish.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 -23 With respect to testing IOLs using such systems, the body of literature is limited. 14,19,22,24 Liu et al 14 initially demonstrated that an IOL could impede growth to some degree using the human capsular bag system developed in Norwich. In the present study, we made a modification in the protocol such that the capsular bag containing the IOL was inverted, resulting in the anterior capsule being closest to the plastic dish.…”
Section: Discussionmentioning
confidence: 99%
“…The development of capsular bag models allowed for the introduction of an IOL (Cleary et al, 2010;Dawes et al, 2012;De Groot et al, 2005;Duncan et al, 1997;Eldred et al, 2014;Liu et al, 1996) and thus provide an alternative experimental system for IOL development and importantly permit IOLs to be tested in a human system. For example, the capsular bag model served as an invaluable tool in the development of the Bag-in-the-lens IOL developed by Prof. Tassignon (De Groot et al, 2005), which is now commercially available. Pedagogic changes have been made to the model that have further improved its value in IOL development.…”
Section: Capsular Bagsmentioning
confidence: 99%
“…There may also be a place for modified implantation techniques and improved IOL designs. 70 Childhood cataract remains an important but treatable cause of potentially lifelong visual handicap. Those privileged to work with affected children have a duty to provide them with the best possible care.…”
Section: Complicationsmentioning
confidence: 99%